(untitled) (Praxis Educativa, 2026)
This article aims to analyze the value that young students in public secondary schools in the city of La Plata, Buenos Aires province, attribute to affectivity in relation to the approaches and implementation of National Comprehensive Sexual Education Law No. 26,150 and Provincial Law 14,744. It seeks to identify the limitations and scope in the construction of interventions focused on coexistence and situations of suffering within the school framework, emphasizing the importance of valuing affectivity. It is observed that practices shaped in light of this statement have implications for affective trajectories and school biographies. In their testimonies, students share everyday experiences that highlight the relevance of the relational, bonding, and affective dimension in school.